Exporting and foreign direct investment spillovers: Cambodia's experience - Sokty Chhair; Luyna Ung (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
One feature of exporting firms in Cambodia is that they are not of domestic origin but are foreign firms that export from the moment they are established in Cambodia. In this paper we examine the extent to which the presence of foreign-owned export firms impacts on the productivity of domestic firms. We consider two channels: first, the extent to which export-induced improvements in the legal and institutional framework has led to productivity improvements for non-exporting firms, and second the extent to which horizontal spillovers from foreign-owned firm's impact on the productivity of domestic firms. We find that relieving institutional constraints for export firms has positive impacts on the productivity of all firms, including non-export firms, and that there are negative productivity spillovers from foreign-owned to domestic firms.
Keywords: D22; F14; O12; O14; 330; exports; foreign direct investment; institutional constraints; spillovers; Cambodia